EFFECT OF DIFFERENT SHADING INTENSITIES AND GENOTYPES ON PRODUCTION OF LEAFY CORIANDER IN OFF SEASON - C.SARADA (The Journal of Research ANGRAU, 2023)
The investigation was under taken to study the effect of different intensities of shade as one factor and promising genotypes as another factor in Factorial Randomized Block Design with three replications during the years 2009-10 and 2010-11. Among the treatments, days taken for germination was observed significantly less under 50% shade (9.88 days) followed by 75% shade (11.04 days). With regard to genotypes, Sadhana germinated earlier (11.20 days) being on par with other genotypes. Number of leaves was recorded significantly more under 50% and 75% shade (6.11) than control (4.41). Among the genotypes significantly more number of leaves were recorded in LCC- 244 (6.43) being on par with LCC- 234 (6.12) than Sadhana (4.81) i.e. check. Significantly maximum yield was recorded with 50% shade (3.59 t ha-1) followed by 35% shade (3.01 t ha-1) than control (0.51 t ha-1). Among the genotypes, significantly maximum yield was recorded in LCC- 244 (3.18 t ha-1) being on par with LCC-234 (2.89 t ha-1) than check (1.87 t ha-1).